Global volcanic hazards and risk - Loughlin, Susan C.; Sparks, R. S. J. (Robert Stephen John), 1949-; Brown, Sarah K.; Jenkins, Susanna F.; Vye-Brown, Charlotte (Cambridge : Cambridge University Press, 2015)
Originally prepared for the United Nations Office for Disaster Risk Reduction, this is the first comprehensive assessment of global volcanic hazards and risk, presenting the state of the art in our understanding of global volcanic activity. It examines our assessment and management capabilities, and considers the preparedness of the global scientific community and government agencies to manage volcanic hazards and risk. Particular attention is paid to volcanic ash, the most frequent and wide-ranging volcanic hazard. Of interest to government officials, the private sector, students and researchers, this book is a key resource for the disaster risk reduction community and for those interested in volcanology and natural hazards. A non-technical summary is included for policy makers. Regional volcanic hazard profiles, with invaluable information on volcanic hazards and risk at the local, national and global scale, are provided online. This title is available as an open access eBook via Cambridge Books Online.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Open Access title.
Keywords: Volcanic hazard analysis; Volcanoes